2023
DOI: 10.54536/ajcp.v2i2.1612
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Control and Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is the rampant onset of diabetes and related complications; chronic kidney disorders and end-stage renal disease are progressing in more than 10% of the world population and mostly affect the elderly, women, minorities and patients with diabetes and hypersensitivity. The early stages of CKD are typically quiet; thus, many people are unaware they have the condition. Data for this review was gathered from Google Scholar, Scopus, PubMed, Elsevier, Cochrane, Sage, Medline, and Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(62 reference statements)
0
0
1
Order By: Relevance
“…In our study, HIV was the strongest signi cantly associated factor with kidney function impairment. Unlike other studies, we did not nd an association between diabetes mellitus [29,51] and kidney function impairment, smoking [9,52,53], body mass index (BMI), socioeconomic status (monthly household income) [44,54] or prior diagnosis of tuberculosis [55] [56] as other studies did. Unlike these previous studies, in our study, fewer participants reported a history of smoking, and there were fewer diabetic patients.…”
Section: Discussioncontrasting
confidence: 95%
“…In our study, HIV was the strongest signi cantly associated factor with kidney function impairment. Unlike other studies, we did not nd an association between diabetes mellitus [29,51] and kidney function impairment, smoking [9,52,53], body mass index (BMI), socioeconomic status (monthly household income) [44,54] or prior diagnosis of tuberculosis [55] [56] as other studies did. Unlike these previous studies, in our study, fewer participants reported a history of smoking, and there were fewer diabetic patients.…”
Section: Discussioncontrasting
confidence: 95%